The Cooperatives as an Alternative Partners for Social and Economic Development: Its Perceived Attainment to the Sustainable Development Goals(SDG) - Carbonel, Loneza Gas-ib - (International Journal of English Literature and Social Sciences (IJELS), 2019)
Abstract: This study focused on the assessment of the socioeconomic status and analysis of the financial and social services of the four(4) selected cooperatives in Tabuk City, Kalinga, Philippines. The descriptive and empirical method was used in the study . The extracted data included the following indicators of the Cooperatives’ financial reports such as the following: Assets, Deposits, and Loans, Net Surplus, Dividends and Patronage refunds.It also conducted a survey from the selected 300 cooperative members on the level of participation of the Cooperatives to the attainment of the Sustainable Development Goals (SDG) of the Philippines.The objectives of the study are summarized as follows : to describe the profile of the cooperatives in terms of its assets, number of members, and age;to determine the members’ economic participation according to their average assets, share capital, deposits, and gross surplus,to determine the members’ economic benefits of the four cooperatives ;to identify the percentage of participation in social and financial obligations of the four cooperatives, and to find out the percentage of contribution the cooperatives have contributed to the sustainable development goals (SDG) as partners for social and economic development of the country. This study found that: the Cooperatives have generated a total of four billion worth of assets and a total members of 16,437,the cooperative greatly contributes to its assets,there is a significant difference in the members’ economic participation on the cooperatives’ services. Moreover, the cooperatives extended funds for the needs of communities ,the cooperative as an economic institution had helped a lot as partners for development and provide quality education as well as in sustaining decent work and economic growth, responsible consumption and production, and peace, justice and strong institution. Finally,the percent contribution of the cooperative in attaining the sustainable development goals of the government is at most 49 percent.